Embodied Action Improves Cognition in Children: Evidence from a Study Based on Piagetian Conservation Tasks - Lozada, Mariana; Carro, Natalia (Frontiers in Psychology, 2016)
Converging evidence highlights the relevance of embodied cognition in learning processes. In this study we evaluate whether embodied action (enaction) improves cognitive understanding in children. Using the Piagetian conservation tasks in 6-7 year olds, we analyzed quantity conservation conceptualization in children who were active participants in the transformation process and compared these results to those of children who were mere observers of an adult’s demonstration (as traditionally conducted). The investigation was performed with 105 first-graders. Conservation tasks were demonstrated to half the children, while the other half actively carried out the transformation of matter. Our findings showed that active manipulation of the material helped children recognize quantity invariance in a higher proportion than when the demonstration was only observed. That is, their enactive experience enabled them to comprehend conservation phenomena more easily than if they were merely passive observers. The outcome of this research thus emphasizes how active participation benefits cognitive processes in learning contexts, promoting autonomy and agency during childhood.